2012
DOI: 10.12775/equil.2012.023
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Situation on Photovoltaic Market in Selected Eastern European States after World Crisis in 2011

Abstract: This article researches the situation on the photovoltaic markets in Slovakia, Romania and Hungary. It is focused on market analysis and prediction together with specific conditions on each market. An upward trend on photovoltaic markets is expected due to the favourable conditions given by the national governments and the European Union. However, state legislation harms competitive environment. There are no big differences between customers’ preferences in product features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Photovoltaic (PV) parks are »largescale photovoltaic systems designed to supply merchant power to the electricity grid« (Wolfe 2012, 994). Romania is an ideal location for the installation of the PV systems (Oprea 2008;Pavlíček 2012;Paulescu et al 2013), the most common being photovoltaic parks and solar thermal systems. Production of renewable energy affects the environment and involves the use of land resources (Sliz-Szkliniarz 2013); also, the development of any type of energy project generates direct and indirect effects on the demand of goods and services as well as employment generation (Caldes, Santamaria and Sáez 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photovoltaic (PV) parks are »largescale photovoltaic systems designed to supply merchant power to the electricity grid« (Wolfe 2012, 994). Romania is an ideal location for the installation of the PV systems (Oprea 2008;Pavlíček 2012;Paulescu et al 2013), the most common being photovoltaic parks and solar thermal systems. Production of renewable energy affects the environment and involves the use of land resources (Sliz-Szkliniarz 2013); also, the development of any type of energy project generates direct and indirect effects on the demand of goods and services as well as employment generation (Caldes, Santamaria and Sáez 2009).…”
Section: Introductionmentioning
confidence: 99%
“…hilight loss of farmland as a negative effects of solar park setting up in rural space in terms of land use changes. Pavlíček (2012) analysed markets of some European contries and concluded that the Romanian slow market development is caused by weak education on the photovoltaic technology and by slow bureaucracy in the subsidies system from the EU.…”
Section: Introductionmentioning
confidence: 99%